The Cambridge companion to legal positivism - Spaak, Torben; Mindus, Patricia (Cambridge University Press, 2021)
"Although the subject-matter of jurisprudence (sometimes called 'legal theory') is not understood in precisely the same way everywhere, everyone agrees that the question of the nature of law falls within the purview of jurisprudence. The central question is, 'What is law?', or 'What is the nature of law?', and it is usually here that one encounters legal positivism and its main challenger, natural law theory, for the first time. The central question in the debate between legal positivists and natural law thinkers - the perennial finalists in the world cup of legal theory - is often said to concern the relation between law and (true) morality: Whereas natural law thinkers maintain that law is necessarily moral, that there is a necessary connection between law and morality, legal positivists hold instead that the relation between law and morality is contingent, that law is sometimes moral, sometimes immoral, and argue that the question of whether we have an obligation to obey the law can be answered only after we have considered the content and the administration of the law in the relevant jurisdiction"--
"...to hold conferences at Stockholm University in November 2018 and April 2019, at which the contributors to the present volume presented draft chapters." - (Acknowledgements)
Keywords: Konferenzschrift -- 2018 -- Stockholm; Konferenzschrift -- 2019 -- Stockholm; Hochschulschrift; Rechtspositivismus